2021
DOI: 10.1080/21505594.2021.1963909
|View full text |Cite
|
Sign up to set email alerts
|

The promise of endogenous and exogenous riboflavin in anti-infection

Abstract: To resolve the growing problem of drug resistance in the treatment of bacterial and fungal pathogens, specific cellular targets and pathways can be used as targets for new antimicrobial agents. Endogenous riboflavin biosynthesis is a conserved pathway that exists in most bacteria and fungi. In this review, the roles of endogenous and exogenous riboflavin in infectious disease as well as several antibacterial agents, which act as analogues of the riboflavin biosynthesis pathway, are summarized. In addition, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 131 publications
(145 reference statements)
0
16
0
Order By: Relevance
“…In addition, B vitamins also have value in patients with kidney disease, sepsis, and COVID-19 ( 44 46 ). Our previous review summarized the anti-infection effect of RF and suggested that RF may have direct antimicrobial effects ( 14 ). Here, in vitro and in vivo phenotypic investigations confirmed that RF has anti- Candida ability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, B vitamins also have value in patients with kidney disease, sepsis, and COVID-19 ( 44 46 ). Our previous review summarized the anti-infection effect of RF and suggested that RF may have direct antimicrobial effects ( 14 ). Here, in vitro and in vivo phenotypic investigations confirmed that RF has anti- Candida ability.…”
Section: Discussionmentioning
confidence: 99%
“…RF deficiency results in cleft lip, glossitis, and oral mucosal edema; it can also affect gastrointestinal and brain function, as well as the metabolism of other vitamins (such as folate, niacin, pyridoxine, and vitamin B 12 ) ( 13 ). Besides its classic role, RF also has application prospects in the field of anti-infection ( 14 ). Since RF is a photosensitizer, RF-mediated photodynamic therapy has an inhibitory effect on microbial keratitis ( 14 ), as well as infections caused by Escherichia coli , Listeria monocytogenes , Plasmodium falciparum , Staphylococcus aureus , and dengue virus ( 15 19 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…92 Riboflavin, perhaps by supporting mitochondrial activity, plays a role in elevating heat shock proteins as an inherent defense against microbial challenges by acting as an agonist of MHC-related protein-1, which in turn facilitates mucosal-associated invariant T cells. 93 Motor neurons are selectively impaired during riboflavin deficiency states by which hypomagnesemia along with low magnesium may impede ATP production. In case studies, riboflavin at 150 mg/day improved muscle strength and reduced plasma lactate and alanine concentrations in a patient with mitochondrial complex I deficiency.…”
Section: Part 2 Addressing Infection and Mitochondrial Dysfunctionmentioning
confidence: 99%
“…97 It is interesting to note that riboflavin has been shown to reduce the virulence of E. coli and S. aureus, and the production of pro-inflammatory cytokines induced by lipopolysaccharide. 93,98 Analogues of the riboflavin biosynthesis pathway, such as roseoflavin, have been shown to exert bactericidal effects by targeting and downregulating the ribolavin riboswitch in bacteria. 99 Carnitine also plays an important role in energy metabolism and has been shown to improve inspiratory capacity.…”
Section: Part 2 Addressing Infection and Mitochondrial Dysfunctionmentioning
confidence: 99%